Patient and Public Involvement for Dementia Research in Low- and Middle-Income Countries: Developing Capacity and Capability in South Asia - Miah, Jahanara; Sheikh, Saima; Francis, Rachel C.; Nagarajan, Gayathri; Antony, Sojan; Tahir, Maryam; Sattar, Rabia; Naz, Anum; Tofique, Sehrish; Billah, Mostazir; Saha, Sajib; Leroi, Iracema (Frontiers in Neurology, 2021)
Background: Patient and public involvement (PPI) is an active partnership between the public and researchers in the research process. In dementia research, PPI ensures that the perspectives of the person with ‘lived experience’ of dementia are considered. To date, in many lower- and middle-income countries (LMIC), where dementia research is still developing, PPI is not well known nor regularly undertaken. Thus, here, we describe PPI activities undertaken in seven research sites across South Asia as exemplars of introducing PPI into dementia research for the first time. Objective: Through a range of PPI exemplar activities, our objectives were to: (1) inform the feasibility of a dementia-related study; and (b) develop capacity and capability for PPI for dementia research in South Asia. Methods: Our approach had two parts. Part 1 involved co-developing new PPI groups at seven clinical research sites in Indian, Pakistan and Bangladesh to undertake different PPI activities. Mapping onto different ‘rings’ of the Wellcome Trust’s ‘Public Engagement Onion’ model. The PPI activities included planning for public engagement events, consultation on the study protocol and conduct, the adaptation of a study screening checklist, development and delivery of dementia training for professionals, and a dementia training programme for public contributors. Part 2 involved an online survey with local researchers to gain insight on their experience of applying PPI in dementia research. Results: Overall, capacity and capability to include PPI in dementia research was significantly enhanced across the sites. Researchers reported that engaging in PPI activities had enhanced their understanding of dementia research and increased the meaningfulness of the work. Moreover, each site reported their own PPI activity-related outcomes, including: (1) changes in attitudes and behaviour to dementia and research involvement; (2) best methods to inform participants about the dementia study; (3) increased opportunities to share knowledge and study outcomes; and (4) adaptations to the study protocol through co-production. Conclusions: Introducing PPI for dementia research in LMIC settings, using a range of activity types is important for meaningful and impactful dementia research. To our knowledge, this is the first example of PPI for dementia research in South Asia.